Expression of microRNAs in leukocytes and serum of asbestosis patients - Kauschke, Vivien; Philipp-Gehlhaar, Monika; Schneider, Joachim; Justus Liebig University Giessen (My University, 2023)
Background: Although asbestos use is banned in many countries, long latency of asbestos-related diseases like pleural plaques or asbestosis mean it is still a public health issue. People suffering from these diseases have a higher risk of developing mesothelioma or lung cancer, which can progress quickly and aggressively. MicroRNAs were suggested as potential biomarkers in several diseases. However, in asbestosis, blood microRNAs are less explored. Since miR-32-5p, miR-143-3p, miR-145-5p, miR-146b-5p, miR-204-5p and miR-451a are involved in fibrotic processes and in cancer, expression of these microRNAs was analyzed in leukocytes and serum of asbestosis patients. Methods: MicroRNA expression was analyzed in leukocytes and serum of 36 patients (26 affected by pleural plaques and 10 by asbestosis) and 15 healthy controls by real-time RT-PCR. Additionally, data analyses were performed regarding disease severity based on ILO classification. Results: MicroRNA miR-146b-5p was significantly down-regulated in leukocytes of patients suffering from pleural plaques with a large effect indicated by η2p = 0.150 and Cohen’s f = 0.42, a value of difference of 0.725 and a 95% confidence interval of 0.070–1.381. In patients suffering from asbestosis miR-146b-5p was not significantly regulated. However, data analyses considering disease severity only, revealed that miR-146b-5p was significantly down-regulated in leukocytes of mildly diseased patients compared to controls with a large effect indicated by η2p = 0.178 and Cohen’s f = 0.465, a value of difference of 0.848 and a 95% confidence interval of 0.097–1.599. Receiver operating characteristic (ROC) curve and an area under the ROC curve value of 0.757 for miR-146b-5p indicated acceptable discrimination ability between patients suffering from pleural plaques and healthy controls. Less microRNAs were detectable in serum than in leukocytes, showing no significant expression differences in all participants of this study. Moreover, miR-145-5p was regulated significantly differently in leukocytes and serum. An R2 value of 0.004 for miR-145-5p indicated no correlation in microRNA expression between leukocytes and serum. Conclusion: Leukocytes seem more suitable than serum for microRNA analyses regarding disease and potentially cancer risk assessment of patients suffering from asbestos-related pleural plaques or asbestosis. Long-term studies may reveal whether down-regulation of miR-146b-5p in leukocytes might be an early indicator for an increased cancer risk.
Keywords: ddc:610